AB1086 The prevalence and the reactivation rates of hepatitis in patients who are taking an immunesupressive agent for treatment of a rheumatological disease. (15th June 2017) - Coskun, BN; Yagız, B; Ermurat, S; Danaci, ES; Tufan, AN; Dalkilic, E
Abstract : Background: Today, the immunosuppressive treatment agents became important for therapy of rheumatoid diseases. Theoretically, the use of these agents may result in reactivations be in patients that infected with Hepatitis B (HBV) and Hepatitis C (HCV) virus. Objectives: We aimed to study the reactions during treatment and prevalence of HBV and HCV infections in rheumatology patients who are using immunosuppressive treatment. Methods: The records of a total of 1146 patients who were taking an immunosuppressive treatment for a rheumatoid disease were reviewed retrospectively. The hepatitis serology, type of immunosuppressive treatment, the duration of treatment, liver function tests, complete blood count; HBV – DNA and HCV – DNA and antiviral agents and time of use (if patient is infected) were recorded. Results: There were 682 (59.5%) women and 464 (40.5%) men, the mean age was 45.04±13.13. Ankylosing spondylitis (AS) was diagnosed in 453, rheumatoid arthritis (RA) in 365, psoriatic arthritis in 151, systemic lupus erythematosus in 43, vasculitis in 39, Behçet Disease in 26, systematic sclerosis in 18, myositis in 9, juvenile rheumatoid arthritis in 7, Sjögren Syndrome in 7, Still Disease in 3, familial mediterian fever in 6, retroperitoneal fibrosis in 1 and mixed connective tissue disease in 1 patient. The rate of HbsAg positivity was 1.8% in AS and 2.2% in RA; the rate of HCV positivity was 0.7% and 1.9% respectively. While HBsAg, AntiHBs and anti-HBcIgG was tested for 898 patients, in 28 patients (2.4%) HBsAg and AntiHBs were negative and anti-HBcIgG was positive. The liver function tests were increased in two occult hepatitis patients, and lamivudine was administered for one and tenofovir for another patient. HCV-RNA was found negative in 12 of 18 patients that positive for HCV. Only one patient had ribavirin + interferon treatment and no reactivation was detected during follow up. The mean length of immunsuppressive treatment was 22.26±18.21 months for HBV positive patients, 19.43±21.40 months for HCV positive patients and 20.94±19.7 months for occult hepatitis. Furthermore, we 10.1% of the patients were vaccinated, 13.4% had natural immunity and 50.7% of patients has not encounter with virus. Conclusions: HBV prevelance was 3.99% and HCV prevelance was 0.95% in general population, although there is difference according to geographical region in our country. HBV prevelance was the highest 9.9% in southeast region and the lowest 0.7 – 2.5% in west region. Low HBV prevelance could be associated with included patients that was young and stay in west region. Because hepatit virus can be reactivate under immunsupressive treatment, patients should be scanned and be careful for occult hepatitis in these scans. References: Vassilopoulos D, Calabrese LH. Viral hepatitis: review of arthritic complications and therapy for arthritis in the presence of active HBV/HCV. Curr Rheumatol Rep. 2013 Apr;15(4):319. Chen YM, Chen HH, Chen YH, Hsieh TY, Hsieh CW, Hung WT, Lan JL, Chen DY. A comparison of safety profiles of tumour necrosis factor α inhibitors and rituximab therapy in patients with rheumatoid arthritis and chronic hepatitis C. Ann Rheum Dis. 2015 Mar;74(3):626–7. Acknowledgements: None. Disclosure of Interest: None declared